The environmental impact of living cultural heritage (intangible heritage) and its role in reducing unemployment in the local community of Khyber - Naqshabandi, Eyad Anwar; Tarifi, Nabil (Journal of Economic, Administrative and Legal Sciences, 2025)
The study illustrates the environmental contributions of living cultural heritage in Khaybar Governorate and how much it contributed to the solution of the unemployment problems and gave self-sufficiency to society.A descriptive analytical method was applied through a questionnaire survey of 300 locals and experts on heritage to measure the dimensions of both the environmental and economic contributions of living cultural heritage. The findings show the importance that intangible cultural heritage gives to the sensitivity of the environment, the promotion of practices that ensure sustainability, and the introduction of new jobs in traditional crafts and cultural tourism. It also significantly contributes to reducing unemployment. Participants emphasize the need for integrated strategies toward preservation and upgrading for the purposes of sustainable development. To implement environmental education, the best way would be through enhanced promotion of local economic initiatives and more engagement between governments, academia, and civil society to come up with workable preservation strategies for both environmental and economic sustainability in Khaybar Governorate.
Keywords: Living cultural heritage; environmental impact; unemployment; sustainable development; traditional crafts; environmental awareness; economic sustainability; cultural tourism; local community